PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT.PERKEBUNAN NUSANTARA V ROKAN HULU - Adityo, Robby; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to analyze the incentives and its influence on the performance of employees prdouction part of PT.Perkebunan Nusantara V Rokan Hulu. Insentives as a variable (X), and employee performance as a variable (Y). The method in this research is descriptive and quantitative using SPSS 20 program, where the sample used is PT.Perkebunan Nusantara V Rokan Hulu production employee which amounted to 60 people and data collection technique through questionnaire. The results of analysis using validity test, reliability test, test of determination of simple linear regression test and t test. So it can be concluded that the incentives significant effect on the performance of production employee of PT.Perkebunan Nusantara V Rokan Hulu.Keywords: Incentives, and Employee Performance.